Stakeholder Insights on Malaria Elimination Strategies in Pangandaran, West Java: a Qualitative Analysis - Faridah, Lia; Fauziah, Nisa; Adams, Fayyaza Faiz; Mufida, Hasna; Akbar, Muhamad Lazuardi; Salsabila, Pricillia Laurenza; Rufinus, Wilbert Bernardi; Virajati, Abimanyu Athallah; Angga, Anggisti Nurdinda Chaerany Putri; Mahira, Khansa; Zahra, Ridha Beta (Universitas Islam Bandung, 2024)
Indonesia has launched a determined effort to eliminate malaria by 2023, focusing on Java and Bali. Despite these efforts, Pangandaran in Java still faces malaria cases. This study aims to meticulously delve into the intricacies of the malaria elimination program's implementation while conducting a comprehensive evaluation of its effectiveness. Structured interviews were conducted with key stakeholders responsible for the malaria program in Pangandaran to extract invaluable insights. The study, carried out in November 2022, followed qualitative research with narrative analysis to reveal nuanced narratives from the participants. Findings from this rigorous analysis revealed a harmonious alignment between the malaria control program in Pangandaran and the Indonesian Ministry of Health guidelines. The strategy to combat malaria vectors in Pangandaran included mosquito net distribution, strategic larvicide application, and educational campaigns like Malaria Awareness Society (MASAMA). The expectation is that the current effective control program will resonate within the Pangandaran community, ultimately leading to the realization of the 2023 elimination target.